2015
DOI: 10.1371/journal.pone.0116754
|View full text |Cite
|
Sign up to set email alerts
|

In-Vivo Nonlinear Optical Microscopy (NLOM) of Epithelial-Connective Tissue Interface (ECTI) Reveals Quantitative Measures of Neoplasia in Hamster Oral Mucosa

Abstract: The epithelial-connective tissue interface (ECTI) plays an integral role in epithelial neoplasia, including oral squamous cell carcinoma (OSCC). This interface undergoes significant alterations due to hyperproliferating epithelium that supports the transformation of normal epithelium to precancers and cancer. We present a method based on nonlinear optical microscopy to directly assess the ECTI and quantify dysplastic alterations using a hamster model for oral carcinogenesis. Neoplastic and non-neoplastic norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The MPAM-SHGM system used for this study has been described previously (29, 34). Illumination was provided using a titanium sapphire (Ti:sapphire) femtosecond (~100fs, 82MHz) laser (Tsunami, Spectra Physics), tunable within 750–1000nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MPAM-SHGM system used for this study has been described previously (29, 34). Illumination was provided using a titanium sapphire (Ti:sapphire) femtosecond (~100fs, 82MHz) laser (Tsunami, Spectra Physics), tunable within 750–1000nm.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we reported on the use of in vivo MPAM-SHGM to delineate 2D cross-sectional morphology of the ECTI (akin to histology) in a hamster model for OED (29). An ECTI line-shape parameter (ΔLinearity, a measure of ECTI curviness) was defined and shown to increase from normal to OED.…”
Section: Introductionmentioning
confidence: 99%
“…premalignancy and oral malignancy imaging through multiphoton microscopy which was combined with OCT, optical Doppler tomography (ODT). By using autofluorescence phenomenon, multiphoton autofluorescence microscopy (MPAM) applied for hamster oral mucosal neoplasia [13]. This group was successfully demonstrated quantitative aspects of oral cancer in a hamster model.…”
Section: Multi-photon Excitation Fluorescence (Mpef)mentioning
confidence: 99%
“…This group was successfully demonstrated quantitative aspects of oral cancer in a hamster model. Also recently in 2016, there was a development of multiphoton microscopy (MPM) for oral epithelial dysplasia based on MPAM by the same group [13]. This method was non-invasive and very important, because this dysplasia could progress to cancer [14].…”
Section: Multi-photon Excitation Fluorescence (Mpef)mentioning
confidence: 99%
“…In an effort to overcome the limitations of COE and autofluorescence imaging, several modalities have been explored including nonlinear microscopy [16,17], Raman spectroscopy [18,19], fluorescence lifetime imaging (FLIM) [20,21], optical coherence tomography [22,23], spectroscopy with point spectrometers [24,25], multispectral imaging [26,27] and confocal microscopy [20,28]. While each of these methods delivers valuable information to aid in the diagnosis of oral cancer, studies have suggested that a combination of these techniques could improve performance [5,7,21,27].…”
Section: Introductionmentioning
confidence: 99%